On a class of recursive-based binomial coefficient identities involving harmonic numbers - Kirschenhofer, Peter; Larcombe, Peter J. (Utilitas Mathematica, 2007)
A particular class of binomial coefficient identities, which involve Harmonic numbers, can be generated in two different ways recursively. In this paper we present several approaches to the recurrence equations which underpin such formulations. A variety of arguments from different branches of combinatorial theory are used.